Hydro-dynamically modified seeding for micro-PIV - Błoński, S.; Domagalski, P.; Dziubiński, M.; Kowalewski, T.A. (Archives of Mechanics, 2011)
This paper presents numerical and experimental analysis of the hydrodynamic flow focusing in a rectangular microchannel. Aim of the study is to improve performance of the Particle Image Velocimetry (PIV) technique applied to micro-scale flow analysis. The symmetric flow focusing system of two channels crossed at right angle is investigated. The numerical model is used to analyse the effect of Reynolds number on the flow focusing mechanism. In the experiment, the flow focusing is applied to concentrate seeding tracers into a thin sheet at the channel axis. Such a modification removes the out of focus images of the seeding particles, effectively improving PIV evaluation of vector fields in microchannel. Based on the experimental and numerical results we have found that expected improvement is possible for the flow at Reynolds number less than 10 only.